Censorship detected in IR (Iran) - Voidly (2026)
CRITICAL severity censorship detected in Iran. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: IR-2026-2319
Keywords: censorship; IR; censorship; critical